Analysis of Students’ Mathematical Critical Thinking Skills in Solving Contextual Problems - Sri Bintang Robiatul Adawiyah; Lia Yuliawati; Agus Jaenudin; Arifin Arifin (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
Mathematical critical thinking ability is an essential skill that students must possess in solving contextual problems. However, students’ mathematical critical thinking ability is still considered low because students are more accustomed to solving problems procedurally rather than conducting analysis and evaluation. This study aims to analyze the mathematical critical thinking ability of vocational high school students based on Facione’s indicators. The study employed a qualitative descriptive method involving 23 eleventh-grade students of SMK Budi Mandiri Tanjungsari as the research subjects. The research instruments consisted of a mathematical critical thinking ability test, interviews, and documentation. The results showed that 65% of students were in the low category and 17% were in the very low category. Students demonstrated fairly good ability in the indicators of interpretation and analysis; however, they were still weak in the indicators of evaluation and inference. Therefore, mathematics learning needs to emphasize evaluative and reflective thinking processes.